Pengaruh Pendidikan Kesehatan Reproduksi Terhadap Tingkat Pengetahuan Remaja Tentang Kesehatan Reproduksi Di MTs. Miftahul Falah Bekasi Tahun 2023 - Siti Sumarni; Dewita Rahmatul Amin (Jurnal Rumpun Ilmu Kesehatan, 2024)
WHO data shows that one fifth of the world's population are teenagers aged 10-19 years, of which 900 million are in developing countries. Adolescence is a transition period from childhood to adulthood. Adolescents tend to become more focused on attracting the attention of the opposite sex in order to gain an understanding of aspects of sexuality. Lack of knowledge about reproductive health can cause various problems, one of which is the occurrence of unwanted pregnancies (KTD), abortion, early marriage and marriage, STIs or STDs and HIV/AIDS. The aim of this research is to determine the influence of reproductive health education on adolescent knowledge about reproductive health at MTs. Miftahul Falah Bekasi in 2023. The research method used is the Pre-experimental One Group With Pre-Post Test Design method. Sampling was taken using purposive sampling as many as 47 respondents. Data analysis used frequency distribution and Wilcoxon test. This research uses primary data from filling out questionnaires by respondents. The results of this study show a p value of 0.102 > 0.05. The conclusion is that Ha is rejected or Ho is accepted, meaning there is no significant influence on providing health education on increasing teenagers' knowledge about reproductive health at MTs. Miftahul Falah Bekasi in 2023. It is hoped that this research will become a reference for increasing teenagers' knowledge about reproductive health and can be used as a reference for increasing knowledge and intensive approaches for teachers and students. It is hoped that the results of this research can serve as policy guidelines for schools to provide comprehensive health education in schools that includes accurate and evidence-based information about reproductive health, including the risk of sexually transmitted diseases, contraceptive methods, and the importance of healthy relationships.